Wudulink / Mohamad Ihsan Ilias - Ilias, Mohamad Ihsan (Universiti Teknologi MARA, Kedah, 2025)
WUDULINK is a compact, modular communal ablution product designed to assist displaced Muslims in flood transfer centers. Addressing the limitations of existing ablution facilities, WUDULINK offers an efficient, space-saving solution, enabling more people to perform ablution simultaneously. Prioritizing compactability, modularity, and efficiency, the design incorporates Islamic elements such as halftone arabesque patterns and minaret-inspired forms within a minimalist aesthetic. Unlike traditional portable ablution bottles, WUDULINK boasts a larger water capacity of approximately 15 liters, foldable storage, and dual flexibility for use with direct water sources or manual refilling. Its connectable design allows multiple units to form a mini ablution station, maximizing water efficiency and functionality in overcrowded spaces. This innovative product bridges the gap between individual and communal ablution needs, offering a practical alternative to existing infrastructure. Its modern design ensures seamless integration into flood center environments while maintaining visual appeal. WUDULINK redefines humanitarian products by enhancing the flood center experience for Muslims, ensuring access to essential religious practices in challenging situations.